Research approach to the organization of educational process in college as a condition for student’s self-development - Хмеляр, Інеса Макарівна (Pedagogy of Higher and Secondary Education, 2015)
Hmelyar I. M. Research approach to the organization of educational process in college as a condition for student’s self-development. The adaptation of research approach as one of the conditions for student’s self-development in the educational process of medical colleges is revealed and proved. It is determined that the research approach in learning activity contributes to character education for self-actualization and professional growth in the conditions of reforming of modern society.